Learning Of Music Tradisional Patrol With Creative Music Garap Method Based On Dolanan Songs - Jarmani, Jarmani; Rusijono, Rusijono; Bachtiar Saiful Bahri (CV. Inara, 2022)
This research created a music-garap innovative compositional content patrol aimed at piquing students' attention since the songs performed are conventional, but the modern, which is a current favorite among children, is also a song dolanan in the form of creative music. This thesis employs development analysis (development research), a research technique for developing a product and evaluating its efficacy and solution using qualitative ethnomusicology bundled under the garap definition.